Hydrogenation of the liquid organic hydrogen carrier compound dibenzyltoluene – reaction pathway determination by 1H NMR spectroscopy. Issue 3 (29th February 2016) - Do, G.; Preuster, P.; Aslam, R.; Bösmann, A.; Müller, K.; Arlt, W.; Wasserscheid, P.
Abstract : The catalytic hydrogenation of the LOHC compound dibenzyltoluene (H0-DBT) was investigated by 1 H NMR spectroscopy in order to elucidate the reaction pathway of its charging process with hydrogen in the context of future hydrogen storage applications. Abstract : The catalytic hydrogenation of the LOHC compound dibenzyltoluene (H0-DBT) was investigated by 1 H NMR spectroscopy in order to elucidate the reaction pathway of its charging process with hydrogen in the context of future hydrogen storage applications. Five different reaction pathways during H0-DBT hydrogenation were considered including middle-ring preference (middle-side-side, MSS), side-middle-side order of hydrogenation (SMS), side-ring preference (SSM), simultaneous hydrogenation of all three rings without intermediate formation and statistical hydrogenation without any ring preference. Detailed analysis of the 1 H NMR spectra of the H0-DBT hydrogenation over time revealed that the reaction proceeds with a very high preference for the SSM order at temperatures between 120 °C and 200 °C and 50 bar in the presence of a Ru/Al2 O3 -catalyst. HPLC analysis supported this interpretation by confirming an accumulation of H12-DBT species prior to full hydrogenation to H18-DBT with middle ring hydrogenation as the final step.